Cloning and Characterization of the Autoinducer Synthase Gene from Lipid-Degrading Bacterium Cedecea neteri - Tan, Kian-Hin; How, Kah-Yan; Tan, Jia-Yi; Yin, Wai-Fong; Chan, Kok-Gan (Frontiers in Microbiology, 2017)
The process of intercellular communication among bacteria, termed quorum sensing (QS), is mediated by small diffusible molecules known as the autoinducers. QS allows the population to react to the change of cell density in unison, in processes such as biofilm formation, plasmid conjugation, virulence, motility and root nodulation. In Gram-negative proteobacteria, N-acyl homoserine lactone (AHL) is the common “language” to coordinate gene expression. This signalling molecule is usually synthesized by LuxI-type proteins. We have previously discovered that a rare bacterium, Cedecea neteri, exhibits AHL-type QS activity. With information generated from genome sequencing, we have identified the luxIR gene pair responsible for AHL-type QS and named it cneIR. In this study, we have cloned and expressed the 636 bp luxI homologue in an Escherichia coli host for further characterization. Our findings show that E. coli harboring cneI produced the same AHL profile as the wildtype C. neteri, with the synthesis of AHL known as N-butyryl-homoserine lactone. This 25 kDa LuxI homologue shares high similarity with other AHL synthase from closely-related species. This work is the first documentation of molecular cloning and characterization of luxI homologue from C. neteri.